Corrigendum to the paper: Doprinos teorije shema i socio-konstruktivističkog pristupa u nastavi: usvajanje funkcionalizma kod studenata na prevodilačkim predmetima - Eraković, Borislava R.; Topalov, Jagoda P. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The authors of this article would like to issue a corrigendum regarding а slip in the title of the summary in English (p. 284). The correct title is: Contribution of Schema Theory and Social-Constructivist Approach to Teaching: the Acquisition of Functionalism Among Students in Translation Courses.